Troubled waters. - Stone, Daniel
In 2008, a team of researchers used satellite images and modeling software to make a complete portrait of human effects on the ocean. Five years later they did it again, capturing a comprehensive view of an ocean in transition.
Keywords: Climatic changes -- Environmental aspects